A reference model for mobile social software for learning. (14th January 2008) - De Jong, Tim; Specht, Marcus; Koper, Rob
This paper provides a reference model for mobile social software and uses it to analyse the current state-of-the-art in its applications for learning. A general overview of the literature in the field and the available projects will be given. The reference model for mobile social software helps us to (1) find out to what extent mobile social software for learning has already been used until date, (2) identify gaps and limitations in current research and provide new ideas and innovative approaches for learning based on these gaps, and (3) position our current research work in preparation of a study of applications of mobile social software for learning. After describing the current state-of-the-art, its limitations and suggestions for future research, an implemented solution of mobile social software for learning is briefly described. The paper concludes with an outlook on possible chances and challenges for future research.